Pengaruh Trauma Masa Lalu terhadap Kesehatan Mental Seseorang - Ningsih, Klara Putri; Putri, Cici Ramadhani; Lubis, Siti Khairuna Salwa (Lembaga Yasin AlSys, 2024)
Trauma on human mental health, refers to the inevitable conflict, stress and frustration in social life. This phenomenon, although common, can cause an imbalance in interpersonal relationships which can lead to mental health problems. Trauma, regardless of age, occupation or skin color, occurs as a result of painful situations, both physical and psychological. The definition of trauma by Evi Sukmaningrum, Psi., Msi, highlights the individual nature of reactions to traumatic events. In the context of mental health, especially in developing countries, this problem is still not given adequate priority. Therefore, this research aims to explore the impact of trauma, explore the role of interpersonal relationships, and respond to the urgent need to increase attention to mental health problems, especially in the context of developing countries. Mental health as an integral part of human well-being is in the global spotlight, but major challenges are visible, especially in developing countries. Traumatic situations in many cases create long-term scars in the memory and subconscious mind, according to the understanding by Evi Sukmaningrum, Psi., Msi. This research seeks to approach mental health problems as an integral part of overall health, with the hope of finding effective approaches to prevention and treatment.